EU Member States’ Position on Data Protection - Mach, Martin (Central European Academy Law Review, 2025)
The European Union places a strong focus on the protection of personal data through European law. This is an important and sensitive area that requires clear rules through legal regulation. However, within the same legal area, the Member States can act from different positions. For example, in the case of the right to be forgotten, a State, or its institutions, is only the appellate authority, while private companies are the first decision-makers. Conversely, in the case of the European Commission’s proposal to combat child sexual abuse, a relatively strong position is expected from the State, which should be able to intervene at its discretion in the privacy, including the personal data, of its citizens. This article thus focuses on the different legal positions of the Member States in the area of data protection and tries to determine whether a stronger or a weaker position of a Member State is better for the protection of personal data.